2021
DOI: 10.1007/s00520-021-06678-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing utilization of cancer rehabilitation services among older breast cancer survivors in the USA: a qualitative study

Abstract: Purpose Many older breast cancer survivors experience long-term disability due to cancer and cancer-related treatments. However, less than 20% of older breast cancer survivors utilize cancer rehabilitation services to address cancer-related disability. Further understanding of survivor experiences may reveal strategies to improve uptake cancer rehabilitation services in the USA. Methods Older breast cancer survivors were recruited from university-based registries, previous breast cancer research studies at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Despite research and recommendations supporting rehabilitation and exercise during and after BC treatment, less than 20% of individuals receive this essential survivorship care [22]. National and global barriers include a dearth of specialized oncology physical therapists and community-based specialty clinics, as well as a lack of established collaboration among oncology healthcare providers and rehabilitation providers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite research and recommendations supporting rehabilitation and exercise during and after BC treatment, less than 20% of individuals receive this essential survivorship care [22]. National and global barriers include a dearth of specialized oncology physical therapists and community-based specialty clinics, as well as a lack of established collaboration among oncology healthcare providers and rehabilitation providers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite availability12 and survivors' desire to receive services for cancer-related disability,13 few older individuals surviving breast cancer access, or engage in, cancer rehabilitation interventions. A recent thematic analysis found that access to rehabilitation services in this population may be affected by factors such as provider interactions, social support, and emerging awareness of disability 14. However, findings from this work did not identify how various elements of intervention or service delivery influence utilization of services 14…”
mentioning
confidence: 76%
“…These facts highlight the need to address the constraints and barriers experienced by patients and healthcare services. One of the reasons proposed to explain this low level of access to physiotherapy is the lack of knowledge among health professionals of the correct use of physiotherapy in functional rehabilitation [25]. Some studies report that only in a quarter of the cases, functional impairments are detected by oncologist and referral to rehabilitation services [26].…”
Section: Discussionmentioning
confidence: 99%